2018 Joint Propulsion Conference 2018
DOI: 10.2514/6.2018-4896
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Linear Energy Deposition Using Femtosecond Laser Filamentation in a M=3 Supersonic Flow.

Abstract: The goal of this study is to demonstrate experimentally the "Laser Spike" concept in a supersonic flow. The "Laser Spike" uses a thin filament of plasma created by a femtosecond laser. This plasma filament formed by the TeraWatt laser pulse acts as a linear energy deposition upstream of the shock wave created by a blunt body. It has been found that the laser energy deposition induces a significant transient reduction of the drag. This reduction has been quantified using a drag balance. These experiments have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…For optical discharges, the intense laser pulse propagating over large distances creates the low density and high temperature filament upstream of the blunt body. The recent experimental study showed that the plasma filament created by the ultrashort laser pulse forms a low-density region that interacts with the bow shock [16]. A number of recent numerical studies also confirmed the formation of vorticity on the interaction of low density region and bow shock, that results a modulation of drag coefficient and flow separation in the high speed flows [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 88%
“…For optical discharges, the intense laser pulse propagating over large distances creates the low density and high temperature filament upstream of the blunt body. The recent experimental study showed that the plasma filament created by the ultrashort laser pulse forms a low-density region that interacts with the bow shock [16]. A number of recent numerical studies also confirmed the formation of vorticity on the interaction of low density region and bow shock, that results a modulation of drag coefficient and flow separation in the high speed flows [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 88%
“…Здесь ν c -транспортная частота столкновений электронов с другими частицами (нейтральными В связи с прогрессом в развитии фемтосекундных лазеров [90] в последнее время также появились предложения воздействовать на сверхзвуковой поток с помощью тонких плазменных филаментов, образуемых при пробое воздуха под действием тераваттного лазерного излучения фемтосекундной длительности [91]. При этом создается сильнонеравновесная плазма высокой (~10 17 см -3 ) концентрации, при распаде которой в наносекундном диапазоне происходит импульсный нагрев газа [92].…”
Section: а)unclassified
“…Локальное энерговложение в сверхзвуковой поток газа позволяет воздействовать на характер обтекания различных тел [1-6]: уменьшать коэффициент лобового сопротивления; увеличивать коэффициент подъемной силы, тем самым увеличивая аэродинамическое качество; совершенствовать управление летательным аппаратом; проводить интенсификацию перемешивания, смену режима течения в пограничном слое. Вклад энергии в набегающий сверхзвуковой поток может осуществляться при помощи различных видов разрядов [7][8][9][10][11]: лазерная искра, микроволновый разряд, электрический межэлектродный разряд, диэлектрический барьерный разряд.…”
Section: Introductionunclassified